PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 165 PEKANBARU - Marhadi, Hendri; ', Yusilawati; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the low value of math studies of class IV elementary school 165 Pekanbaru, because the teacher use konvensional method. Based on these problems, it is necessary given way to solve the problem include applying cooperative learning type Numbered Heads Together (NHT). Subjects in this research were 40 students of class IV of 165 elementary school Pekanbaru. This research was conducted in two cycles, by doing the daily test of the end of each cycle. The result of first cycle show that the teacher’s activity was good and student activity was good too but must increase in activ student and teamwork. In second cycle, the teacher and student activity is better and the student more active than before. The result of this research shows that the average value of students before action is 64,37 later in the cycle I is 76,12 and the second cycle increased to 80,37. It means that the implementation of cooperative learning type Numbered Heads Together (NHT) can increase math studies of class IV of 165 elementary school Pekanbaru.Keywords : Numbered Heads Together(NHT), Mathematics Learning Outcomes.